2004
DOI: 10.2298/jmmb0401041b
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cobalt and nickel from zinc sulphate solutions using activated cementation

Abstract: The influence of different parameters (duration, temperature, zinc dust quantity, concentration of activators - copper and antimony) on the process of activated cementation of Co and Ni has been studied. We have worked with industrial zinc sulphate solutions. During the process of activated cementation of Co and Ni, copper (involved as CuSO4.5H2O) and antimony (involved as Sb2O3) were used as activators. The lowest values of Co content have been obtained at a temperature of 80-85 oC, CCu = 200-300 mg/dm3 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…At higher copper concentrations, the zinc surface was covered in copper eliminating the reaction sites available for cementation to take place. The results in this work are in agreement with Boyanov et al [18] in that the addition of copper did not significantly improve cobalt cementation.…”
Section: Influence Of Copper Ion Concentrationsupporting
confidence: 93%
See 4 more Smart Citations
“…At higher copper concentrations, the zinc surface was covered in copper eliminating the reaction sites available for cementation to take place. The results in this work are in agreement with Boyanov et al [18] in that the addition of copper did not significantly improve cobalt cementation.…”
Section: Influence Of Copper Ion Concentrationsupporting
confidence: 93%
“…Parameters that are known to affect cementation reactions are pH, temperature, activator concentration, and zinc dust quantity [12,13,[17][18][19][20][21]. Van der Pas et al [17] concluded that the optimal conditions for cementation in a solution containing 30 mg/L cobalt were 30 mg/L copper and 1.5 mg/L antimony (both as activators) as well as addition of 4 g/L zinc at a solution temperature of 70°C.…”
Section: à ð3þmentioning
confidence: 99%
See 3 more Smart Citations